2018
DOI: 10.18203/2394-6040.ijcmph20182972
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge of medical emergency in dental clinic in Saudi Arabia: a cross sectional study

Abstract: Background: In dentistry most of the medical emergency considered to be mild, and in some situation it can be very serious. The objective of our study is to assess knowledge and awareness of dental general practitioner, preparedness of dental clinic/team and the prevalence of most common medical emergencies encountered in dental clinics.Methods: This is a cross sectional study using self-administrated electronic questionnaire conducted on dental general practitioners (GPs) working in kingdom of Saudi Arabia du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…2 Rafee LA et al concluded similarly when they evaluated the dental UG final year students and strongly emphasized incorporating practical training in the teaching curriculum. 3 In the study conducted by Ahamed A et al among the undergraduate students found that they had a good knowledge about the various medical emergencies and their management but they lacked confidence in the practical aspect of the same concluding that it is essential to incorporate hands-on courses to improve the confidence of the UG students which was similar to the results observed by Albelaihi HF et al 2 , Akbari N et al 4 Similar conclusions were given by Azad A et al 5 and Sheikho MA et al 6 among general dental practitioner's knowledge regarding medical emergency situations was average as compared to those who had attended emergency workshops and it is essential to conduct training courses and workshops more often for graduated dental practitioners. 5,7 An analytical survey study conducted among dental interns provided various observations including a lack of knowledge on medical emergencies in southern India dental schools.…”
Section: Discussionsupporting
confidence: 65%
“…2 Rafee LA et al concluded similarly when they evaluated the dental UG final year students and strongly emphasized incorporating practical training in the teaching curriculum. 3 In the study conducted by Ahamed A et al among the undergraduate students found that they had a good knowledge about the various medical emergencies and their management but they lacked confidence in the practical aspect of the same concluding that it is essential to incorporate hands-on courses to improve the confidence of the UG students which was similar to the results observed by Albelaihi HF et al 2 , Akbari N et al 4 Similar conclusions were given by Azad A et al 5 and Sheikho MA et al 6 among general dental practitioner's knowledge regarding medical emergency situations was average as compared to those who had attended emergency workshops and it is essential to conduct training courses and workshops more often for graduated dental practitioners. 5,7 An analytical survey study conducted among dental interns provided various observations including a lack of knowledge on medical emergencies in southern India dental schools.…”
Section: Discussionsupporting
confidence: 65%
“…This could be due to higher academic degrees & prior training in cardiac patient treatment were all connected to better knowledge scores [ 10 ]. While low to moderate knowledge scores among D1,D2,D3 students could be due to lower academic levels, minimal clinical exposures to the management of cardiovascular patients, less training & not attending regular updated workshops [ 1 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Saudi Arabia has made it mandatory in the curriculum for all health university programs to complete the BLS course before entering the clinics [ 21 ]. One of the studies revealed that very few dental practitioners have a comprehensive understanding of BLS [ 1 ]. Evidence, however, shows that dentists' BLS abilities degrade quickly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations